THE MOYO DANCE OF NIAS FROM THE PERSPECTIVE OF SOCIAL THEOLOGY AND ECOTHEOLOGY: CRAFTING A NARRATIVE OF ECOLOGICAL SPIRITUALITY IN THE ERA OF CLIMATE CRISIS - Zalukhu, Amirrudin (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2025)
The global climate crisis calls for a renewed narrative of ecological spirituality that fosters harmonious relationships among humanity, nature, and the Divine. In response, this study examines the Moyo Dance, a traditional ceremonial dance from Nias, Indonesia, through the lenses of social theology and ecotheology, aiming to cultivate ecological awareness rooted in local culture. Rich in symbolic meaning, the Moyo Dance reflects deep interconnections between human beings and the natural world, offering insights into values of cosmic harmony, courage, and gratitude that are urgently relevant to contemporary environmental challenges. Employing a qualitative methodology, this research integrates cultural analysis, symbolic interpretation, and theological reflection on the dance's movements and rituals. The study reveals that the Moyo Dance is not merely a form of cultural expression but also a living manifestation of ecological spirituality. It conveys a theological understanding of humanity's vocation as stewards of creation, aligning with both biblical and indigenous worldviews. The findings suggest that the ecological values embodied in the Moyo Dance can enrich social theology and Christian education, especially in contexts seeking to bridge faith, culture, and environmental responsibility. This research advocates for the inclusion of the Moyo Dance in educational initiatives and intercultural dialogue as a means of promoting ecological sustainability. Ultimately, the Moyo Dance offers a valuable contextual contribution to the global discourse on theology and climate action.